Evolocumab Added to Statin Is Associated With Intracranial Atherosclerotic Plaque Regression Compared With Statin Alone - Xinzhi Hu; Yiyang Liu; Weizhuang Yuan; Zongmuyu Zhang; Shun Li; Anqi Cheng; Qiuyu Yu; Haoyao Guo; Yinxi Zou; Mingli Li; Caiyan Liu; Yan Xu; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background We aimed to investigate the effects of evolocumab, a proprotein convertase subtilisin/kexin type‐9 inhibitor for intensive lipid‐lowering, on intracranial atherosclerotic stenosis. Methods From a prospectively established high‐resolution magnetic resonance imaging database, consecutive patients with intracranial atherosclerotic stenosis (≥50%) with 2 detections of high‐resolution magnetic resonance imaging over 6 months were included in this retrospective analysis. Eligible patients were grouped by treatment: evolocumab add‐on (evolocumab+) versus no evolocumab (evolocumab−). The primary outcome was plaque response (plaque regression >5%). Secondary outcomes included the percentage of changes in plaque burden and stenosis degree. Logistic and linear regression analyses were used to estimate the association between evolocumab use and the above outcomes in both the general and subgroup (intensive versus nonintensive statin) analyses. Results Among 179 statin‐treated patients (50 evolocumab+, 129 evolocumab−), evolocumab add‐on therapy was associated with higher plaque response (68.0% versus 34.1%), greater plaque burden reduction (median [interquartile range]: −8.2% [−11.4%, −1.8%] versus –1.9% [−6.7%, 4.4%]), and stenosis degree reduction (−15.3% [−33.7%, −1.3%] versus –5.4% [−25.8%, 12.3%]). Adjusted regression analyses showed significant associations between evolocumab use and plaque response (odds ratio [95% CI], 6.67 [2.80, 16.91]), plaque burden reduction (estimate [95% CI], −7.0% [−11.5%, −2.5%]), and stenosis degree reduction (estimate [95% CI], −20.3% [−31.7%, −7.0%]). Subgroup analyses according to background statin intensity showed consistent associations. Conclusions Evolocumab add‐on therapy over 6 months was associated with intracranial atherosclerotic plaque regression compared with statin therapy alone. However, given the retrospective design and potential between‐group differences, these findings require further confirmation in prospective randomized controlled studies.